1997
DOI: 10.1093/nar/25.20.4098
|View full text |Cite
|
Sign up to set email alerts
|

CD, absorption and thermodynamic analysis of repeating dinucleotide DNA, RNA and hybrid duplexes [d/r(AC)]12.[d/r(GT/U)]12 and the influence of phosphorothioate substitution [published erratum appears in Nucleic Acids Res 1997 Nov 1;25(21):4429]

Abstract: Circular dichroism (CD) spectra and melting temperature (Tm) data for five duplexes containing phosphorothioate linkages were compared with data for four unmodified duplexes to assess the effect of phosphorothioate modification on the structure and stability of DNA. DNA and DNA.RNA duplexes. Nine duplexes were formed by mixing oligomers 24 nt long in 0.15 M K+(phosphate buffer), pH 7.0. Unmodified DNA.DNA and RNA.RNA duplexes were used as reference B-form and A-form structures. The CD spectra of the modified h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
33
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 20 publications
13
33
0
Order By: Relevance
“…An overall similarity of the DNAzyme/RNA complex spectra (Fig. 6C) to that typical for A-type RNA/DNA hybrids was observed (25). This finding also confirms an earlier observation based upon various Mg 2ϩ -free DNAzyme complexes that the hybrid nature of the flanking arms strongly influences their global geometry (24).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…An overall similarity of the DNAzyme/RNA complex spectra (Fig. 6C) to that typical for A-type RNA/DNA hybrids was observed (25). This finding also confirms an earlier observation based upon various Mg 2ϩ -free DNAzyme complexes that the hybrid nature of the flanking arms strongly influences their global geometry (24).…”
Section: Discussionsupporting
confidence: 88%
“…Addition of a complementary RNA strand resulted in raising a regular positive Cotton effect at 269 nm, i.e. a region typical of the DNA/RNA hybrids (25). Influence of an increased Mg 2ϩ concentration on a double helical structure is not strong but clearly visible, as indicated by the increase in amplitude of the Cotton effect.…”
Section: Study Of Ion-induced Folding Of the Dnazyme By Fluorescence mentioning
confidence: 95%
“…In addition, we found that incorporation of two or three modifications led to detrimental DT m values between 13 and 16 C each, thus suggesting that this may be a reasonable temperature range to predict the effect of this modification in oligonucleotides of RNA. We also confirmed the known stability trend on canonical homo-and hetero-duplexes (RNA:RNA > RNA:DNA > D-NA:DNA), 35,36 and found that the effect of the modification on homo-or hetero-duplexes is independent of structure.…”
Section: Discussionsupporting
confidence: 83%
“…This would account for the observed selectivity of D, R* and A strands for DD and DR duplexes, over RD and RR duplexes. Furthermore, there is ample evidence that [DR, DD] and [RD, RR] duplexes belong to different conformational families (45)(46)(47)(48)(49). The work of Gray and co-workers (45) and others (47,48) have shown dramatic CD differences in the spectra of RD…”
Section: Discussionmentioning
confidence: 99%